Research progress survey on interactive evolutionary computation - Pei, Yan; Takagi, Hideyuki (Journal of ambient intelligence and humanized computing, 2024)
We report our research progress on interactive evolutionary computation (IEC). Following description of IEC features, we present our research on IEC user modeling, acceleration of IEC search, several IEC frameworks, evolutionary multi-objective optimization with IEC, and IEC for human science. IEC research is categorized into three fields in general; major part of IEC papers is IEC application-oriented research; almost all the others are research that aims to reduce IEC user fatigue; and very little work researches the use of IEC for human science. In particular, IEC is a data analysis and processing method and tool for the discovery of human psychological and physiological knowledge. We include several of our IEC application-oriented research projects in this paper, and focus on two other research directions, i.e., IEC algorithm research to reduce user fatigue, and IEC for human science research.